PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 5 KOTA SOLOK - Astuti, Widya; Haryono, Yulia; Lovia, Lita (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was conducted based on the studentâs understanding on mathematics concept was still low and the low curiosity of student to the subject material. This research was aimed at revealing wheather the use of Learning Starts With A Question technique could give a better effect on the studentâs understanding on mathematics concept than conventional learning in class VII SMPN 5 Kota Solok. This was an experimental research which used random desain towardÂ subject. The instrument of the research was test on mathematics concept. The data then was the perceived data analysis the perceived data analysis. Based on theÂ data analysis, it was revealed that the sample was distributed normally and had homogeny variant. The result of hypothesis test showed that p-value (0,023) was smaller than indicating that the hypothesis was accepted. Hence, it was concluded that the application of Learning Starts With A Question technique could improve the studentsâ understanding on mathematics concept better than that of the conventional learning.